2017
DOI: 10.1902/jop.2017.170187
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of a Novel Predictive Biomarker Profile for the Outcome of Periodontal Treatment

Abstract: The "fingerprint" of GCF enzymes and bacteria described here offers a way to predict the outcome of non-surgical periodontal treatment on a site-specific basis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 49 publications
(72 reference statements)
2
33
0
Order By: Relevance
“…Only 4 of the 36 biomarkers had at least three classifications in at least three articles, and it was on these that the meta‐analyses were performed. These molecules were all enzymes: matrix metalloproteinase (MMP) 8, 1907 control and target conditions/13 classifications/six articles (Baeza et al, ; Gul, Douglas, Griffiths, & Rawlinson, ; Gul et al, ; Leppilahti et al, ; Mäntylä et al, ; Yuan, Liu, & Zheng, ); elastase, 1660/five/five (Eley & Cox, , ; Gul et al, , ; Ito et al, ); cathepsin, 1146/three/three (Eley & Cox, , ; Gul et al, ); trypsin, 1146/three/three (Eley & Cox, , ; Gul et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only 4 of the 36 biomarkers had at least three classifications in at least three articles, and it was on these that the meta‐analyses were performed. These molecules were all enzymes: matrix metalloproteinase (MMP) 8, 1907 control and target conditions/13 classifications/six articles (Baeza et al, ; Gul, Douglas, Griffiths, & Rawlinson, ; Gul et al, ; Leppilahti et al, ; Mäntylä et al, ; Yuan, Liu, & Zheng, ); elastase, 1660/five/five (Eley & Cox, , ; Gul et al, , ; Ito et al, ); cathepsin, 1146/three/three (Eley & Cox, , ; Gul et al, ); trypsin, 1146/three/three (Eley & Cox, , ; Gul et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Only 4 of the 36 biomarkers had at least three classifications in at least three articles, and it was on these that the meta-analyses were performed. These molecules were all enzymes: matrix metalloproteinase & Zheng, 2018); elastase, 1660/five/five (Eley & Cox, 1992a, 1992bGul et al, 2016Gul et al, , 2017Ito et al, 2014); cathepsin, 1146/three/three (Eley & Cox, 1992a, 1992bGul et al, 2016); trypsin, 1146/three/ three (Eley & Cox, 1992a, 1992bGul et al, 2016).…”
Section: Synthesis Of the Qualitative And Quantitative Analysis Of mentioning
confidence: 99%
“…Previous reports using samples collected in vivo have suggested that PCR‐based methods result in increases, of up to fivefold, in levels of detection . However, such DNA‐based approaches may have diagnostic relevance as they have been used as part of a panel of biomarkers that may predict the outcome of periodontal treatment . Other approaches used to study the interaction of P. gingivalis with host cells include the use of fluorescently labelled bacteria and flow cytometry .…”
Section: Discussionmentioning
confidence: 99%
“…To determine the invasion efficiency of P. gingivalis using a method not dependent on viable counting, the invasion percentage was calculated using a DNA quantification method . H357 cells were seeded and infected with P. gingivalis NCTC 11834, as described above.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation